2009
DOI: 10.1093/hmg/ddp482
|View full text |Cite
|
Sign up to set email alerts
|

Proteotoxic stress increases nuclear localization of ataxin-3

Abstract: Spinocerebellar ataxia type 3 (SCA3)/Machado Joseph disease results from expansion of the polyglutamine domain in ataxin-3 (Atx3). Atx3 is a transcriptional co-repressor, as well as a deubiquitinating enzyme that appears to function in cellular pathways involved in protein homeostasis. In this study, we show that interactions of Atx3 with valosin-containing protein and hHR23B are dynamic and modulated by proteotoxic stresses. Heat shock, a general proteotoxic stress, also induced wild-type and pathogenic Atx3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
83
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 65 publications
6
83
3
Order By: Relevance
“…Recently, Reina et al demonstrated that MJD protein/ataxin 3 translocated into the nucleus immediately after the heat shock. In this condition, VCP appeared to stay in the cytoplasm (48). It would also be interesting to see whether histone deacetylation could be observed after the heat shock.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, Reina et al demonstrated that MJD protein/ataxin 3 translocated into the nucleus immediately after the heat shock. In this condition, VCP appeared to stay in the cytoplasm (48). It would also be interesting to see whether histone deacetylation could be observed after the heat shock.…”
Section: Discussionmentioning
confidence: 88%
“…However, there is a general elevation in the amount of ubiquitylated protein (229). ATXN3 regulates transcription of multiple genes (65,215), a property which may allow for a coordinated response to proteotoxic stresses, which have been shown to promote nuclear accummulation of ATXN3 (206). In C. elegans, ATXN3 has been linked to the control of longevity by the IGF-I signaling axis (131).…”
Section: Josephin Familymentioning
confidence: 99%
“…In Drosophila, AT3 suppresses poly(Q)-induced neurodegeneration in a catalytic activity-dependent manner (20). Atxn3 knock-out mouse embryonic fibroblasts (MEFs) are more sensitive than wild type MEFs to heat shock (21). In cells, AT3 assists in the proteasomal targeting of endoplasmic reticulum-associated degradation substrates (22,23) and induces aggresome formation (24).…”
mentioning
confidence: 99%